2014
DOI: 10.1117/12.2061104
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous GaN for enhanced solar hydrogen production

Abstract: In this report we present the fabrication of III-nitride devices with nanoporous structure used as photoelectrodes for solar water splitting. Photoelectrochemical etching in a KOH solution of the GaN and InGaN/GaN devices at different concentrations and applied voltages has been employed to fabricate both planar and nanorod devices into nanoporous structures with controllable pore sizes. Photoluminescence measurements of the GaN and InGaN/GaN multi-quantum well (MQW) with nanoporous structures have shown an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Both photocurrent and hydrogen generation were enhanced for GaN with nanoporous structure. NP-GaN can be used as a substitute for noble metal cocatalyst with high cost and low abundance [118][119][120]. NP-GaN as an electrode for photodegradation and hydrogen evolution is excited by external light to form electron-hole pairs, and then the electron-hole pairs are separated to the surface of gallium nitride for redox reactions, due to the increase of surface area to volume ratio.…”
Section: Photocatalysis Energy Storage Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both photocurrent and hydrogen generation were enhanced for GaN with nanoporous structure. NP-GaN can be used as a substitute for noble metal cocatalyst with high cost and low abundance [118][119][120]. NP-GaN as an electrode for photodegradation and hydrogen evolution is excited by external light to form electron-hole pairs, and then the electron-hole pairs are separated to the surface of gallium nitride for redox reactions, due to the increase of surface area to volume ratio.…”
Section: Photocatalysis Energy Storage Materialsmentioning
confidence: 99%
“…It is reported that the porous structure obtained by etching GaN with KOH and changing the etching parameters affected the final electrode performance [119]. With the increase of the porous structure, hydrogen production also increased.…”
Section: Photocatalysis Energy Storage Materialsmentioning
confidence: 99%
“…14,15 The research on NPFs is not limited to GaN: different materials such as nanoporous InGaN, 16−19 Si, 20 carbon membranes, 21 and WO 3 22 have demonstrated a great potential for photoelectrochemical water splitting 18,20,21 and photocatalytic fuel cells. 22 A vast majority of reports on the synthesis of NPFs are focused on different kind of etching of thin films or GaN− sapphire templates such as electroless etching, 3,4 electrochemical etching, 6,10,17 or high-temperature annealing. 8,9 The fabrication of ordered NPFs has been demonstrated using inductively coupled plasma (ICP) etching with an anodic alumina template as etching mask.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The attractiveness of GaN NPFs resides in their significant strain relaxation , and enhanced surface Raman scattering . Comparing with their compact counterparts, GaN NPFs have demonstrated improved properties in diverse applications such as photoelectrochemical water splitting, supercapacitors for energy storage, , light emitting diodes (LEDs), ,, distributed Bragg reflectors, or mechanic removal of films from the substrate. , The research on NPFs is not limited to GaN: different materials such as nanoporous InGaN, Si, carbon membranes, and WO 3 have demonstrated a great potential for photoelectrochemical water splitting ,, and photocatalytic fuel cells …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation